1989
DOI: 10.1071/zo9890665
|View full text |Cite
|
Sign up to set email alerts
|

Host Plant Preferences of Populations of Helicoverpa-Armigera (Hubner) (Lepidoptera, Noctuidae) From Different Geographic Locations

Abstract: Helicoverpa armigera in Australia is found in many different geographic locations and has been recorded on a large number of host plants. We partly investigated the nature of this polyphagy by offering moths from six different sources the same set of host plants in oviposition trials. Laboratory H. armigera ranked the plants offered into the following categories: most preferred-tobacco, maize, sunflower; least preferred-cabbage, pigweed and linseed; intermediate-soybean, cotton and lucerne. Moths reared from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
33
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 0 publications
4
33
0
1
Order By: Relevance
“…Irrespective of the growth stages of the host species tested, females showed a strong oviposition preference for maize and okra and the least preferred host species were pepper and eggplant. The finding in our study that Japanese H. armigera strains exhibit oviposition preference hierarchies is consistent with that reported for the species in other regions (Fenemore and Thanee, 1990;Firempong and Zalucki, 1990b;Ramnath et al, 1992;Zalucki, 1995, 1996). Oviposition preference hierarchies in H. armigera are known to vary between and within geographic populations (Firempong and Zalucki, 1990b;Jallow and Zalucki, 1996).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Irrespective of the growth stages of the host species tested, females showed a strong oviposition preference for maize and okra and the least preferred host species were pepper and eggplant. The finding in our study that Japanese H. armigera strains exhibit oviposition preference hierarchies is consistent with that reported for the species in other regions (Fenemore and Thanee, 1990;Firempong and Zalucki, 1990b;Ramnath et al, 1992;Zalucki, 1995, 1996). Oviposition preference hierarchies in H. armigera are known to vary between and within geographic populations (Firempong and Zalucki, 1990b;Jallow and Zalucki, 1996).…”
Section: Discussionsupporting
confidence: 81%
“…The finding in our study that Japanese H. armigera strains exhibit oviposition preference hierarchies is consistent with that reported for the species in other regions (Fenemore and Thanee, 1990;Firempong and Zalucki, 1990b;Ramnath et al, 1992;Zalucki, 1995, 1996). Oviposition preference hierarchies in H. armigera are known to vary between and within geographic populations (Firempong and Zalucki, 1990b;Jallow and Zalucki, 1996). Therefore, further studies are needed to elucidate whether geographically distant or isolated populations of H. armigera in Japan show similar or different preferences for host plants.…”
Section: Discussionsupporting
confidence: 81%
“…Singer et al (1992) showed that for Euphydryas editha, an oligophagous insect species, variation among individual females in acceptance of a second-ranked host species could be caused either by variation in strength of preference for the top-ranked host over the secondranked host, and/or by variation in the general readiness to oviposit. Polyphagous species such as Helicoverpa armigera (Hübner) also display a hierarchy of host plant preference (Firempong and Zalucki 1990a;Jallow andZalucki 1995, 1996;Jallow 1998), and the pattern of host utilisation by individual females may vary in response to changes in physiological state.…”
Section: Introductionmentioning
confidence: 99%
“…Linalool is a common floral volatile in many mothpollinated plants and has been shown to have both attractant (Raguso et al, 2003;Suckling et al, 1996) and deterrent (Kessler and Baldwin, 2001) properties in ovipositing Lepidoptera. Linalool is a major component of the floral odour of tobacco (Loughrin et al, 1990), a preferred host of H. armigera (Firempong and Zalucki, 1990) and is also produced in small quantities from vegetative tissue volatile blends in response to herbivore attack (De Moraes et al, 2001). At high concentrations, linalool can be toxic to a variety of insect species (Abdelgaleil et al, 2009;Chang et al, 2009;Phillips et al, 2010), affecting mortality, growth, activity and feeding in lepidopteran larvae (Rajwinder et al, 2010;Singh et al, 2009).…”
Section: Introductionmentioning
confidence: 99%